Gerakan Buruh Sejak Proklamasi Sampai 1965 - IRMAYANI, T. (Politeia: Jurnal Ilmu Politik, 2011)
The story of labor movement in Indonesia is an interesting event in the 1950s and early 1960s. At that time there were hundreds of labor organizations and dozens of labor union federation. This study aimed to discuss the history of the labor movement in Indonesia through 1945-1965. The study found that in the 1950s the conflict of the labor movement has always happened. This happens because the workers become members of political parties. But in the 1960s the con-flict has ended. This phenomenon is influenced by five things: (1).Workers are placed in the Companys Board; (2). Most of the workers directly under the control of the Army, espe-cially those belonging to the BKS-BUMIL; (3).The companies are controlled directly and under the supervision of military; (4).The weakening of political parties which was originally a shelter of labor unions; (5). Labor included in the Parliament (Dewan Perwakilan Rakyat Gotong Royong/DPR GR).Keywords: Labor movement, political conflict, political parties.